2010
DOI: 10.1371/journal.pgen.1001177
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Blood Pressure Extremes Identifies Variant near UMOD Associated with Hypertension

Abstract: Hypertension is a heritable and major contributor to the global burden of disease. The sum of rare and common genetic variants robustly identified so far explain only 1%–2% of the population variation in BP and hypertension. This suggests the existence of more undiscovered common variants. We conducted a genome-wide association study in 1,621 hypertensive cases and 1,699 controls and follow-up validation analyses in 19,845 cases and 16,541 controls using an extreme case-control design. We identified a locus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
249
7
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 336 publications
(284 citation statements)
references
References 41 publications
15
249
7
2
Order By: Relevance
“…The association of lower BP and increased sodium reabsorption appeared counterintuitive. 8 In our result, the minor G allele of rs13333226 was associated with higher DBP in a communitybased Chinese population; this result is opposite to those found with other cohorts. We therefore tested whether the UMOD gene correlated with renal sodium excretion.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The association of lower BP and increased sodium reabsorption appeared counterintuitive. 8 In our result, the minor G allele of rs13333226 was associated with higher DBP in a communitybased Chinese population; this result is opposite to those found with other cohorts. We therefore tested whether the UMOD gene correlated with renal sodium excretion.…”
Section: Discussioncontrasting
confidence: 99%
“…One study from the European cohorts found that the minor G allele of rs13333226 was associated with a lower risk of HTN. 8,25 However, in these cohorts, the minor G allele of rs13333226 is associated with lower urinary UMOD excretion and lower urinary sodium excretion. The association of lower BP and increased sodium reabsorption appeared counterintuitive.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…[34][35][36][37][38] On the contrary, heritability of hypertension and BP-related traits seems higher 18 and GWAS have reported different SNPs highly significantly associated with BP even if with quite low effect size in terms of mmHg. [19][20][21]39 This evidence could support the hypothesis that the genetic component of stroke susceptibility that is mediated by hypertension is quite diluted. Another hypothesis is that rarer variants in genes implicated in Mendelian forms of stroke may have larger effects.…”
Section: Discussionsupporting
confidence: 71%
“…This has already been apparent in the first large genome-wide association study by the Wellcome Trust Case-Control Consortium [87] where the study of all other complex diseases resulted in significant and plausible hits whereas not a single genetic variant achieved genome-wide significance for hypertension. Only with changes in study designs [88] and further increased sample sizes [89] have genomic studies in hypertension evolved into a success story.…”
Section: Precision Medicine and The Role Of Proteomics In Hypertensionmentioning
confidence: 99%